POTENSI RIZOBAKTERI YANG DIISOLASI DARI RIZOSFIR TANAMAN GRAMINAE NON-PADI UNTUK MEMACU PERTUMBUHAN BIBIT PADI - Maulina, Ni Made Intan; Khalimi, Khamdan; Wirya, Gusti Ngurah Alit Susanta; Suprapta, Dewa Ngurah (Journal of Agricultural Science and Biotechnology, 2015)
Rice ( Oriza sativa L.) is the main food for Indonesian people, however the rice production is not enough to fulfill all national demand. Rice productivity in Indonesia was about 4,5 ton/ha, relatively low when compared to other rice growing countries such Australia, Japan, and China. It is necessary to find a measure to increase the rice productivity in Indonesia. One of the Measure is the use of rhizobacteria isolated from the rhizozpheres of the plants belongs to the family Graminae. This study was done in order to find potential rhizobacteria from rhizospheres of five plant species belong to the family Graminae, namely Cymbopogon ciatrus , Imperata cylindrica , Saccharum officinarum, Pennisetum purpureum and Schizostachum mosum . Result of this study showed that 10 isolates of rhizobacteria obviously increased the number of lateral roots of rice seedling cultivar Ciherang. The rice seedling treated with isolate Al7Kla produced the highest number of lateral roots when compared to other isolates. This isolate may be used to promote the rice growth in order to increase the yield.
Keywords: rhizobacteria, lateral root, rice growth